Correlation Between Emotional Intelligence and Blood Groups Among Medical Students - Chakraborty, Ruma; Khair, Rummana; Sankar Roy Biswas, Rajat; Kumar Bhattacharjee, Pabitra (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Emotional intelligence, known as emotional quotient or EQ, is the ability to understand, use and manage your own emotions in positive ways to relieve stress, communicate effectively and empathize with others. There are numerous lines of evidence that show the influence of blood groups on skills and abilities related to EQ. This study aims to compare the EQ-related skills and abilities among medical students with various blood groups. Materials and methods: This cross sectional study was conducted in the Department of Anatomy, Chattagram Maa-O-Shishu Hospital Medical College from November 2021 to May 2022. Sample were collected from Chattagram Maa-OShishu Hospital Medical College and Southern Medical College. The responses are entered as data into the Statistical Package for Social Science (SPSS) version 20 and the qualitative data is analyzed using chi square test and the quantitative data is compared using the Bonferroni version of the ANOVA test. Results: The most frequent blood group is B in this study. Overall, students with blood group AB scored the most with 23.08% of them scoring more than or equal to 120. On the other hand, students of blood group O scored the least, with only 14.81% of them scoring 120 or above. 20.51% of A group and 15.79% of B group scored 120 or more. There was no significant difference between blood groups and emotional intelligence. The highest scores concerning self-awareness, Self-confidence and Self competency are in blood group AB (19.4615 ± 2.79, 18.4615 ± 2.99, 17.6154 ± 2.63 respectively) and p- values are 0.20, 0.15 and 0.94. Students who have A blood group scored higher in motivation and self-control (18.2308 ± 3.56 and18.4103 ± 3.51) and who have blood group B scored higher on empathy (18.7018 ± 2.82 and p- value was 0.99). Conclusion: Subjects with blood group “AB” had a higher degree of emotional Quotient as compared to other blood groups. Blood group Bis the most prevalent blood group in our study population. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 56-59